2015
DOI: 10.1007/s00430-015-0427-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of CMV co-infection in HIV-positive women and their neonates in a tertiary referral centre: a cohort study

Abstract: Co-infection with CMV in HIV-positive pregnant women is associated with perinatal mother-to-child transmission (MTCT) of both viruses. This retrospective study reports on the incidence of maternal and neonatal CMV (presence of anti-CMV IgG and IgM, CMV DNA PCR and/or CMV virus isolation) in high-risk pregnancies due to maternal HIV infection, MTCT of HIV and/or CMV. One hundred and eleven maternal samples and 75 matched neonatal samples were available for HIV and subsequent CMV testing. In this cohort of HIV-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Risk factors for cCMV infection in HIV‐exposed uninfected children have been previously described. Maternal CMV serostatus was not available from these cohorts; however, most HIV‐1‐infected pregnant women are co‐infected with CMV even in resource‐rich countries [Reitter et al, ], and maternal serostatus is a poor predictor of the risk of congenital CMV transmission [Britt, ]. Our findings are consistent with reports that type of maternal antiretroviral therapy is not associated with the rate of cCMV infection [Guibert et al, ; Frederick et al, ], whereas maternal CD4 T cell count <200 cells/mm 3 is independently associated with cCMV infection [Guibert et al, ].…”
Section: Discussionsupporting
confidence: 87%
“…Risk factors for cCMV infection in HIV‐exposed uninfected children have been previously described. Maternal CMV serostatus was not available from these cohorts; however, most HIV‐1‐infected pregnant women are co‐infected with CMV even in resource‐rich countries [Reitter et al, ], and maternal serostatus is a poor predictor of the risk of congenital CMV transmission [Britt, ]. Our findings are consistent with reports that type of maternal antiretroviral therapy is not associated with the rate of cCMV infection [Guibert et al, ; Frederick et al, ], whereas maternal CD4 T cell count <200 cells/mm 3 is independently associated with cCMV infection [Guibert et al, ].…”
Section: Discussionsupporting
confidence: 87%
“…Apart from two exceptions in smaller studies, 19, 25 the cCMV rates among HIV-exposed, uninfected infants in our sub-study were higher than those seen in the majority of other published studies ranging from 2.2% to 4.6% among studies of HIV-exposed infants in the U.S., France, South Africa, Brazil, and Thailand. 11, 1316, 2630 Among HIV-infected infants, cCMV rates correlated with those reported in other studies, which typically ranged from 4.3% to 21%; 11, 12, 14, 16, 29 but included some studies with rates as low as 0% 13 and others with rates as high as 26–29%. 31, 32…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, Manicklal and colleagues did not find any relationship between ARV prophylaxis and congenital CMV infection in HIV-infected infants [11]. However other studies have suggested that there is an effect of ARV prophylaxis on CMV infection [7, 22, 23], cART reduces serological biomarkers of inflammation and immune activation [24, 25]. ARV could impede CMV reactivation in HIV-infected pregnant women and thereby reduce the possibility of CMV transmission to infants born to mothers who took prophylactic regimens.…”
Section: Discussionmentioning
confidence: 99%